PROMOTING STUDENTS’ READING COMPREHENSION IN REPORT TEXT BY USING TABLEAU STRATEGY - Muhammad Khoiri (Universitas Islam Ogan Komering Ilir Kayuagung, 2018)
The aim of the study was to find whether tableu strategy was effective to improve the tenth grade students of SMA Negeri 1 Teluk Gelam or not. The selection of the study sample using purposive sampling so that there were 64 students taken. To collect the data, the reading test in the form of multiple choices was administered. Before giving the test, the test was tried out to non-sample students (class X.3) at SMA Negeri I Teluk Gelam in order to find the validity and reliability of the test. The data were analyzed using t-test after the data were considered normal and homogenous. The result of independent sample t-test showed that t-obtained (3.950) was higher than t-table (1.9990) and pvalue (0.000) was less than αvalue (0.05), it showed that null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It meant that Tableu strategy was effective to improve the tenth-grade students’ reading achievement at SMA Negeri 1 Teluk Gelam. In short, tableu strategy was useful to improve students’ reading achievement because this strategy guided them to comprehend the reading texts given during the treatment by asking and answering the questions posed by their classmates